PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. TIRTA MAHAKAM RESOURCES TBK SAMARINDA - -, Novi Susanti (EKONOMIA, 2019)
The analytical tool in this study uses descriptive analysis methods and quantitative analysis, namely by multiple linear regression analysis. The sample in this study uses simple random sampling using the Slovin formula technique, so the sample taken is 266 samples of permanent employees in the production section of PT. Tirta Mahakam Resources Tbk Samarinda.The results showed that the F value calculated = 143.844, using a significance limit of 0.05, then obtained the significance value was less than 0.05, which is 0.000, this means that simultaneously the variables of work stress and work motivation have a significant effect on employee performance . The coefficient of determination (R2) is 0.522 or 52.2%, then the coefficient simultaneously in explaining the variation or change in the dependent variable (Y) found the magnitude of the influence of the independent variable 52.2%, while the rest is 47.8%.The results of testing the hypothesis (H1) through the calculation results obtained t count value of 15.444 with a significance level of 0.000 results is smaller than 0.05, which means that the hypothesis in this study Ho is rejected and Ha accepted. This test statistically proves that job stress has a positive and dominant effect on employee performance. The results of testing the hypothesis (H2) through the calculation results obtained t count value of 3.215 with a significance level of 0.001 is less than 0.05, which means that the hypothesis in this study Ho is rejected and Ha is accepted. This test statistically proves that motivation has a positive effect on the performance of employees of PT. Tirta Mahakam Resources Tbk Samarinda